SINTESIS PESTISIDA FLUSILAZOL - Aldes Lesbani; Hitoshi Kondo; Yoshinori Yamanoi; Hiroshi Nishihara (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Flusilazole pesticide has been synthesized through coupling reaction of organosilica and aryl halide using palladium catalyst in basic condition under argon atmospherie in two reaction steps. The product was characterized using 1H and 13C NMR spectroscopy at 500 MHz and 125 MHz respectively.The results of this research showed that the high yield of colorless oil product was obtained up to 70%. 1H and 13C NMR spectra have six and eight peaks respectively, which indicate the structure of flusilazole.